2014
DOI: 10.1016/j.trb.2014.06.009
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Random Regret Minimization model

Abstract: This paper presents, discusses and tests a generalized Random Regret Minimization (G-RRM) model. The G-RRM model is created by replacing a fixed constant in the attribute-specific regret functions of the RRM model, by a regret-weight variable. Depending on the value of the regretweights, the G-RRM model generates predictions that equal those of, respectively, the canonical linear-in-parameters Random Utility Maximization (RUM) model, the conventional Random Regret Minimization (RRM) model, and hybrid RUM-RRM s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(137 citation statements)
references
References 16 publications
2
132
2
1
Order By: Relevance
“…Travel mode fairness was elicited by requesting respondents to rate on a 5-point likert scale the quality of their travel time ranging from poor to excellent by transit in comparison with the time by car as the reference travel mode to university and leisure activities. Greater difference between an attribute (i.e., quality of travel time) of the chosen alternative (i.e., transit) versus the foregone alternative (i.e., car) is naturally associated with a higher level of expected regret (Chorus, 2010;Prato, 2014), which is a counterfactual thought that is strongly related to the perception of fairness (Nicklin et al, 2011).…”
Section: Survey Designmentioning
confidence: 99%
“…Travel mode fairness was elicited by requesting respondents to rate on a 5-point likert scale the quality of their travel time ranging from poor to excellent by transit in comparison with the time by car as the reference travel mode to university and leisure activities. Greater difference between an attribute (i.e., quality of travel time) of the chosen alternative (i.e., transit) versus the foregone alternative (i.e., car) is naturally associated with a higher level of expected regret (Chorus, 2010;Prato, 2014), which is a counterfactual thought that is strongly related to the perception of fairness (Nicklin et al, 2011).…”
Section: Survey Designmentioning
confidence: 99%
“…Recently, Chorus (2010) introduced an approach based on Random Regret Minimization (RRM), as a complement to the RUM for the analysis of DCE data. The Random Regret…”
Section: These Studies Base Their Analysis On the Linear-in-parametermentioning
confidence: 99%
“…is the unobserved part of regret Extreme Value Type I-distributed. The observed part of the regret function as described by Chorus (2010), is:…”
Section: Modelling Utility and Regretmentioning
confidence: 99%
See 1 more Smart Citation
“…The regret for any considered alternative j, denoted ( ) Reg j , is the sum of all binary regrets of choosing alternative j over the non-considered alternatives j J  . The random regret minimisation model, proposed in Chorus et al (2008) and subsequently refined by Chorus (2010), has been shown to be able to accommodate the compromise effect.…”
Section: Overview Of the Random Regret Mixed Logit Modelmentioning
confidence: 99%